MOLECULAR DETECTION OF ADHESIVE MATRIX MOLECULES FOR Staphylococcus aureus ISOLATED FROM DIFFERENT SAMPLES - Falah. A. Jafaar; Nuha J. Kandala (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The Staphylococcus aureus is a ubiquitous Gram-positive bacterium, which may resident in various parts of body as a nqiormal flora, but this bacterium can also cause community and nosocomial infections, which enhanced by different virulence factors. Hence, the goal of the recent work is isolation and identification of S. aureus form different sources and investigate the capability of these isolates to synthase microbial surface components recognizing adhesive matrix molecules (MSCRAMs). For achieving this aim, a total of 326 samples were obtained from various clinical sources, including wounds, blood, acne, skin, vagina and gum. Among these samples, only 100 isolates were confirmed as S. aureus, after subjecting to conventional identification techniques as well as molecular detection of nuc gene utilizing PCR technique. The molecular investigation of mecA gene was carried out for confirmation of the methicillin-resistant S. aureus (MRSA). The results show 70 isolates were MRSA and the rest of these isolates were regarded as methicillin-sensitive S. aureus (MSSA). The investigation of virulence factor presence was carried out by molecular detection of nine genes (fnbA, fnbB,eno, ebps, fib, bbp,clfA, clfB, and cna), which encode to MSCRAMs of S. aureus. The findings revealed that the majority of MRSA isolates harbored clfA (52%% of total isolates), followed by eno, clfB, fib, bbp, fnbA, fnbB, ebps, and cna with (35, 34, 33, 25, 22, 21, 19 and 16%), respectively. This study indicates thatdifferent of MRSA isolates may harbor one or more these genes in different distribution.